Structure–Function Relationship of Organic Semiconductors: Detailed Insights From Time-Resolved EPR Spectroscopy - Biskup, Till (Frontiers in Chemistry, 2019)
Organic photovoltaics (OPV) is a promising technology to account for the increasing demand for energy in form of electricity. Whereas the last decades have seen tremendous progress in the field witnessed by the steady increase in efficiency of OPV devices, we still lack proper understanding of fundamental aspects of light–energy conversion, demanding for systematic investigation on a fundamental level. A detailed understanding of the electronic structure of semiconducting polymers and their building blocks is essential to develop efficient materials for organic electronics. Illuminating conjugated polymers not only leads to excited states, but sheds light on some of the most important aspects of device efficiency in organic electronics as well. The interplay between electronic structure, morphology, flexibility, and local ordering, while at the heart of structure-function relationship of organic electronic materials, is still barely understood. (Time-resolved) electron paramagnetic resonance (EPR) spectroscopy is particularly suited to address these questions, allowing one to directly detect paramagnetic states and to reveal their spin-multiplicity, besides its clearly superior resolution compared to optical methods. This article aims at giving a non-specialist audience an overview of what EPR spectroscopy and particularly its time-resolved variant (TREPR) can contribute to unravelling aspects of structure--function relationship in organic semiconductors.